Impacts of regulatory processes on the experiences of carers of people in LGBTQ communities living with mental illness or experiencing a mental health crisis. (June 2019) - Martin, Jennifer; Butler, Meredith; Muldowney, Anne; Aleksandrs, Gabriel
Abstract: This article presents the findings of exploratory research on the mental health and community services experiences of informal/family carers of people from LGBTQ communities living with mental illness, or experiencing a mental health crisis. The aim of the research is to explore the experiences of carers in relation to provisions for carers and people from LGBTIQ communities in the mental health legislation, policy and practice standards in the state of Victoria in Australia. Data were collected from online surveys and in-depth interviews and analysed according to the alignment of the stated intent of these documents and the actual experiences of carers. Highlights: Service provision and worker responses were variable. Carers were not confident that services would be helpful. The services carers wanted were not available or accessible. Many services were provided in restrictive environments and considered harmful. Carers need adequate information to provide care.